Mental Miskin pada Kehidupan Masyarakat Indonesia - Chusnul Khotimah; Sani Safitri (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
Mental poverty is a condition where a person feels less with all the assets he has. Basically, poverty is a condition where a person cannot fulfill his life's needs, but a poor mentality does not occur in poor people alone, many people who are well-off have a poor mentality so that someone can justify any means to make himself richer, it could be by theft, corruption or even other things. In the Qur'an people who have a poor mentality are not praiseworthy because it can make people ungrateful for the wealth they have. Therefore in social life this poor mentality is one of the problems that must be corrected so that in community life it will make it more comfortable and can make the heart calmer. The purpose of this article is to find out the extent of this poor mentality as a social problem by using the literature study method or the method of reading, taking and analyzing journals and books, as well as using the interview method or interviewing humans as objects. The final result of this research is that mental poverty is a social problem that is still very minimal in society's care for it, so it needs solutions from internal and external to overcome it.